Analysis of Quality Management System at MIN 1 Musi Banyuasin (Lembaga Pengembangan Kinerja Dosen, 2025)
The implementation of a quality management system in educational institutions is a strategic step in ensuring the quality of the process and sustainable learning outcomes. However, in reality, many madrasas still face obstacles in implementing the system effectively and comprehensively. This study aims to analyze in depth the quality management system implemented at MTs Negeri 2 Musi Banyuasin, including planning, implementation, evaluation, and strengthening strategies. The research method used is qualitative descriptive with a case study approach, where data is collected through observation, documentation, and in-depth interviews with relevant parties in the institutional structure of the madrasa. The results of the study indicate that the quality management system in this madrasa has adequate structural devices and formal documents, but its implementation is still administrative, not fully integrated into the work culture, and not supported by digitalization of information systems and optimization of stakeholder participation. Strengthening is needed in the aspects of technical training, utilization of technology, and instilling a culture of quality so that the system built can run sustainably and have a real impact on improving the quality of education.